Implementasi Pendidikan Agama Islam Dalam Membangun Nilai-Nilai Relegius Peserta Didik Di SMAN 8 Kota Ternate - Samad, Khaeria A.D.; Agus, Agus; Ilyas, Usman; Zein, Muhammad; Saumur, Amanan S; Alhadar, Muhdi; Umasugi, Nirwan (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the implementation of Islamic Religious Education (PAI) in fostering students’ religious values at SMA Negeri 8 Kota Ternate, identify its challenges, and formulate effective improvement strategies. A descriptive qualitative approach was employed using observation, in-depth interviews, and document analysis. The results show that PAI is implemented through both intraclass and extracurricular activities in an integrated manner, with the teacher playing a central role as a role model. Internal challenges include students’ low spiritual awareness and lack of religious practice at home, while external challenges involve limited facilities and low parental involvement. To address these issues, the school applies strategies such as religious habit formation, integration of religious values across subjects, student leadership in spiritual activities, and partnerships with parents and the community. Effective implementation of PAI requires a comprehensive synergy among all educational elements